(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Birth weight serves as a vital marker of newborn health, influencing long-term well-being. This study delves into the relationship between various maternal and environmental factors and infants’ birth weight. By exploring these multifaceted influences, this research aims to contribute essential insights to prenatal care strategies and public health policies. A comprehensive literature review was conducted to identify relevant maternal variables (such as maternal age, nutrition, prenatal care, and maternal health status) and environmental variables. These variables were then analyzed concerning their impact on infants’ birth weight using rigorous statistical methods. This study underscores the intricate relationship between maternal and environmental variables and infants’ birth weight. The findings emphasize the critical need for targeted prenatal interventions aimed at improving maternal nutrition, mental well-being, and access to prenatal care. Addressing environmental factors, especially in disadvantaged communities, is crucial. By understanding and addressing these multifaceted influences, healthcare providers and policymakers can develop targeted strategies to enhance maternal and child health outcomes, promoting healthier birth weights and, consequently, better long-term health for infants.